2017
DOI: 10.1177/2399808317743971
|View full text |Cite
|
Sign up to set email alerts
|

Changing urban form in a shrinking city

Abstract: This paper uses building footprint data in a shrinking city, Baltimore, MD, in 1972 and 2010 to achieve two primary research objectives. The first is to understand the historical patterns of housing construction and demolition in selected row house neighborhoods in Baltimore between 1972 and 2010. The second is to understand changes in housing footprints, and associations between these changes and physical and socio-economic characteristics in selected neighborhoods. We find that housing losses and associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Tach and Emory (2017) found that the redevelopment of VLs into public housing had significant direct and indirect spillover effects on neighborhood racial and economic composition; VLs in gentrifying neighborhoods were also found to be more likely to be filled by higher-income residents than vacant units in lower-income areas. Relatedly, Hollander et al (2019) found that severely depopulating neighborhoods in Baltimore exhibited significant spatial clustering of VLs. Some hedonic models have examined the effects of converting VLs into nondevelopmental land uses (e.g.…”
Section: Hedonic Modeling: Impacts Of Vl In Low Development Potential Areasmentioning
confidence: 93%
“…Tach and Emory (2017) found that the redevelopment of VLs into public housing had significant direct and indirect spillover effects on neighborhood racial and economic composition; VLs in gentrifying neighborhoods were also found to be more likely to be filled by higher-income residents than vacant units in lower-income areas. Relatedly, Hollander et al (2019) found that severely depopulating neighborhoods in Baltimore exhibited significant spatial clustering of VLs. Some hedonic models have examined the effects of converting VLs into nondevelopmental land uses (e.g.…”
Section: Hedonic Modeling: Impacts Of Vl In Low Development Potential Areasmentioning
confidence: 93%
“…Frazier et al, 2013;Morckel, 2014;Reis et al, 2016;Sakamoto and Yokohari, 2016). According to Hollander et al (2017), who tested whether building demolitions are clustered in row house neighbourhoods in Baltimore, demolition is treated as a proxy for vacant lots since demolished buildings are also popular measures of shrinkage and easily geocoded. By comparing building footprints (polygons that represent building shapes on a two-dimensional plane) in 1972 and 2010, Hollander et al (2017) found that at the parcel level, demolitions were no more clustered than expected, while the opposite was true at the block group level.…”
Section: Introductionmentioning
confidence: 99%
“…The process of population loss and its related problems, collectively termed urban shrinkage , constitutes one of the most pertinent issues in developed countries (Haase et al., 2014, 2017; Hollander, 2011; Hollander et al., 2017; Martinez-Fernandez et al., 2012). The places of urban shrinkage are named shrinking cities and face challenges of ever-increasing demolitions of buildings and vacancies of building lots (Frazier et al., 2013; Haase et al., 2017; Hackworth, 2016; Hollander, 2010; Schetke and Haase, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the second half of the 20 th century, the coupling of rapid suburbanization and disinvestment within urban cores has reshaped the spatial structure of America's cities. A consequence was the deterioration of accessibility for large urban population segments to reaching basic daily amenities [1][2][3][4]. With the suburbanization of residents, businesses, and the tax base more broadly, urban commercial destinations-from personal and health services to healthy restaurant options and retail outlets-have been steadily moving to locations in the more distant metropolitan peripheries.…”
Section: Introductionmentioning
confidence: 99%